Modal Analysis of Corrugated Plate by Finite Element Analysis - Abdul Kudus, Sakhiah (International Journal of Integrated Engineering, 2020)
The use of corrugated steel plates as part of a bridge structure has received worldwide acceptance. Corrugated steel plates are widely utilized as web members of bridge girders for pre-stressed concrete bridges. In the lifetime of such a structure, performance and stability will degrade due to the effects of many factors. This process is usually accompanied by the development of corrosion and loss of thickness in the affected region. This paper aimed to study the vibration characteristics of corrugated web and flanges of bridge girder undergoing corrosion and loss of section problem. The finite element analysis utilizing ABAQUS CAE software has been adapted to model and solve this problem. First, the baseline model of undamaged and healthy corrugated plate was modelled to determine its natural frequency and mode shape. The baseline model results were further used to compare with the damage model. The size of the damage area was fixed, while the position, orientation, and depth of loss of thickness varied for different damage cases. A significant reduction in natural frequency can be observed in the presence of damage to corrugated web bridge girders.